Ruthenium carbenes supported on mesoporous silicas as highly active and selective hybrid catalysts for olefin metathesis reactions under continuous flow - Bru, Miriam; Dehn, Richard; Teles, J. Henrique; Deuerlein, Stephan; Danz, Manuel; Müller, Imke B.; Limbach, Michael (Chemistry - a European journal, 2013)
In the search for a highly active and selective heterogenized metathesis catalyst, we systematically varied the pore geometry and size of various silica-based mesoporous (i.e., MCM-41, MCM-48, and SBA-15) and microporous (ZSM-5 and MWW) versus macroporous materials (D11-10 and Aerosil 200), besides other process parameters (temperature, dilution, and mean residence time). The activity and, especially, selectivity of such “linker-free” supports for ruthenium metathesis catalysts were evaluated in the cyclodimerization of cis-cyclooctene to form 1,9-cyclohexadecadiene, a valuable intermediate in the flavor and fragrance industry. The optimized material showed not only exceptionally high selectivity to the valuable product, but also turned out to be a truly heterogeneous catalyst with superior activity relative to the unsupported homogeneous complex.